DISCOURSES OF HERITAGISATION AND NATIONAL IDENTITY NARRATIVES: A BIBLIOMETRIC MAPPING OF THEORIES, APPROACHES AND INTELLECTUAL STRUCTURES - Hoyos-Alayo, Carlos Antonio; Hoyos-Alayo, Walter Manuel; Hoyos-Alayo, Luz Consuelo (Revista Prâksis, 2026)
Cultural heritage has become a central device for producing social memory and legitimising national identity narratives, yet the scientific evolution of this field had remained fragmented and lacked an integrative mapping. This study quantitatively analysed international research on discourses of heritagisation and national identity narratives in order to identify its temporal development, intellectual structure, leadership, networks and motor themes. A bibliometric mapping was conducted in Scopus, with the search carried out on 4 March 2026, followed by manual screening and processing in Bibliometrix 5.1.1, VOSviewer 1.6.20, Lotka’s law, Bradford’s law and Reference Publication Year Spectroscopy. The final corpus comprised 652 documents from 507 sources published between 1989 and 2026, with 47,461 references, an annual growth rate of 8.58%, a mean document age of 7.1 years, 9.353 citations per document, 1,005 authors, 1.62 co-authors per publication and 9.356% international co-authorship. Output reached its peak in 2025 with 130 articles, the Bradford core grouped 77 sources and 216 articles, and national leadership was concentrated in the United Kingdom with 114 records, the United States with 102 and China with 66. The field shows accelerated consolidation, low authorial concentration, a robust genealogical base and a thematic shift towards cultural heritage, national identity, collective memory and intangible cultural heritage, confirming that heritagisation operates as a multilevel symbolic mediation in the construction of collective identities.